Former Yugoslav Republic of Macedonia : Second Review Under the Stand-By Arrangement and Request for Waiver of Performance Criteria and Rephasing of the Program; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the former Yugoslav Republic of Macedonia. (IMF Staff Country Reports; Country Report, 2007)
This paper discusses the Former Yugoslav Republic of Macedonia's Second Review Under the Stand-By Arrangement and Request for Waiver of Performance Criteria and Rephasing of the Program. The 2007 fiscal deficit target increased modestly to 1 percent of GDP. Taxes were cut and budget quality improved, but there remain fiscal risks, in particular in delivering the planned reduction in transfers and subsidies. Over the medium term, the government aims to keep the fiscal deficit below 1 1\2 percent of GDP, cutting overall government spending by 2 percent of GDP while raising public investment.